Jus ad bellum: A Study of divergent traditions - Ramadhan, Rahma Khamis (Strathmore University, 2017)
Public international law 1, the law of the political system of nation-states and their relations with each other, prohibits the threat and use of force in settling international disputes. Being the foundation of modern international law, the Charter of the United Nations begins by declaring that the primary goal of the UN is to maintain peace and security.2 The threat and use of force with regards to international relations is addressed by the UN Charter under Article 2(4) which provides that: All members shall refrain in their international relations from the threat or use of force against the territorial integrity or political independence of any state, or in any other manner inconsistent with the Purposes of the United Nations.’3Sanctions are invoked against States that resort to the use of force.4 Should a member state be attacked in violation of Article 2(4) above, Article 51 preserves the right of individual or collective self-defense if an armed attack occurs. The right of self-defense was reiterated by the International Court of Justice in the Nicaragua Case where it was held that prohibition on the use of force is covered by treaty, the UN Charter and customary international law. The Court expressly stated that this prohibition is a jus cogens norm, that is, a fundamental principle of international law from which no derogation is ever permitted. 5Jus ad bellum (the right to engage in war) is a set of criteria to be satisfied or consulted prior to initiating or engaging in war in order to determine whether a particular war is permissible and justified. Exceptions to the general rule regarding prohibition of the threat and use of force are provided for under the UN Charter and customary international law
Submitted in partial fulfillment of the requirements of the Bachelorof Laws Degree, Strathmore University Law School